EFEK ANTIDIABETES DAUN JAMBU BIJI PADA HEWAN COBA: TINJAUAN KEPUSTAKAAN SISTEMATIS - oktoviani, oktoviani; sania aulia fasa; ahmad azmi (UNIVERSITAS BENGKULU, 2023)
Background: Indonesia ranks fifth in the world with diabetes and diabetes cases are expected to increase continuously. The treatment of diabetes is taking medication and modifying life style. Herbal medicine is used as an additional or substitute drug for diabetes because of its efficacy and has few side effects. Guava leaf is one of the traditional plants that are widely used by the community. Guava leaves have been used as a treatment for diabetes and hypertension in South Africa. Secondary metabolites found in guava leaves such as flavonoids, phenolics and terpenoids were found to have antidiabetic activity. Previous studies have been conducted, but there was no systematic literature review that discussed the efficacy of the antidiabetic effect administration of guava leaves on experimental animals comprehensively. Methods: This systematic literature review was conducted on three databases, namely Pubmed, Cochrane and Elsevier. Duplicate and irrelevant studies are eliminated, abstracts are screened and followed by reading the entire articles to select journals that fit the inclusion criteria. Critical appraisal uses Joana Brigs Institute tool. Results: There were three articles met the criterias. The result of the three studies showed that administration of guava leaf extract is reported able to reduce blood glucose level and improve sensitivity insulin. Conclusion: Administration of guava leaf extract significantly reduce blood glucose level and improve insulin sensitivity on animal laboratory.